Routine Histopathologic Analysis of Hip and Knee Bone Specimens After Total Joint Arthroplasty. Issue 15 (1st August 2022) - Moschetti, Wayne; Kunkel, Samuel; Schilling, Peter; Jevsevar, David
Abstract : Total hip and total knee arthroplasties (THA/TKA) are some of the most common elective surgeries done in the United States. Routine histopathologic analysis of hip and knee bone specimens after total joint arthroplasty commonly occurs to identify unexpected pathologic findings and serves as a quality assurance measure. As the most common indication for THA and TKA is osteoarthritis, the practice of routine histopathologic analysis may not be routinely warranted. There is no clear consensus on the cost-effectiveness of this practice, and the literature has questioned both the clinical relevance of discrepancies between surgeon diagnosis and histopathological diagnosis and raised concerns about variance in the histological evaluation of resected specimens by pathologists. Femoral head analysis in the setting of femoral neck fractures has been previously reported, yet there is no clear overview for this topic in the setting of elective THA. The histopathologic features of bone specimens during routine total joint arthroplasty, the cost-effectiveness, and current recommendations will be reviewed.